Influence of cultivation methods on the chemical and nutritional characteristics of Lentinula edodes - Cristiane Vieira Helm, Fabiane Bach; Charles Windsnon Isidoro Haminiuk, Edson Alves De Lima, Marcelo Barba Bellettini (Emirates Journal of Food and Agriculture, 2019)
Abstract: Lentinula edodes (Shiitake) is an edible mushroom with excellent nutritional potential, aroma and flavor. It’s traditionally produced on wood logs, but this practice has been replaced by cultivation on axenic substrates (AS) made from different materials that are stored in plastic bags. This papper aimed to evaluate the nutritional composition of L. edodes grown on Quercus acutíssima (QA) and AS by correlating their chemical composition with the media on which they were grown. Culture media were analyzed for their density, moisture content, ash, extractives, lignin (soluble and insoluble) and holocelulose before L. edodes inoculation, as well as after the second consecutive harvest this mushrooms. The mushrooms from the second harvest of each culture media were characterized regarding their moisture content, protein, ash, lipids, dietary fiber (soluble and insoluble), α, β and glucanas total, carbohydrates and minerals. Mushrooms cultivated on AS showed higher protein content, macrominerals and lipids, when compared to mushrooms cultivated on QA. AS initially contained lower lignin content, less holocelulose and a reduced C:N ratio when compared to QA. The results showed that the composition of the culture medium influenced the nutritional composition of L. edodes mushrooms.